INVESTIGATION ON THE CUTTING PARTICLES TRANSPORT IN HORIZONTAL WELL DRILLING - ELTAHIR ELTILIB, RAWIA ABD ELGADIR (2010)
Arguably the most important prerequisite function to permit further progress in well drilling operations up to reach production is a complete removal of drilled cuttings from the well bore. This target becomes more challenging in highly-deviated to horizontal wells, where the cuttings particles have more tendency to accumulate in the lower side of the well bore and form a bed of standstill cuttings. In this study, a mathematical model based on the mechanistic theory and the three-layer approach was developed to simulate the cutting particles transport in annular flow during the horizontal drilling process. Two mathematical models were developed to investigate the cuttings transportation performance in horizontal wells. Due to high non- linearity, both were solved numerically after conversion to computer algorithms using MATLAB. The master model examined the performance of irregular shaped cuttings transported in concentric annulus by non-Newtonian fluids. The model predicted the velocities of the layers, the layer’s concentration, the dispersive shear stress, and the pressure drop. The transport performance was adequately simulated under various operational and design conditions, namely the effect of the cuttings size, cuttings shape, annular size, rate of penetration and the mud rheology in term of fluid viscosity. The second model represented a modified model which used to test the sensitivity of the frictional forces calculations, where empirical correlations were employed to replace Szilas formula to calculate the layers and wall friction stresses. The cuttings size, mud viscosity and annular size demonstrated significant effect on transport process. While the operational rate of penetration performed the lowest effect between the entire parameters of the cuttings transport. The results compared favorably with those obtained by previous investigators. Accordingly, the simulations demonstrated that the basic model could be used to analyze the cuttings transport. Thereby, it could potentially be used as design and/or analysis tools for the follow-up of transport processes in horizontal wells.